Effect of Expiratory Resistive Loading in Expiratory Muscle Strength Training on Orbicularis Oris Muscle Activity - Matsuo, Yoshimi; Yanagisawa, Yukio; Shuntoh, Hisato; Horiuchi, Noriaki (Journal of Physical Therapy Science, 2014)
[Purpose] The purpose of this study was to elucidate the effect of expiratory resistive loading on orbicularis oris muscle activity. [Subjects] Subjects were 23 healthy individuals (11 males, mean age 25.5±4.3 years; 12 females, mean age 25.0±3.0 years). [Methods] Surface electromyography was performed to measure the activity of the orbicularis oris muscle during maximum lip closure and resistive loading at different expiratory pressures. Measurement was performed at 10%, 30%, 50%, and 100% of maximum expiratory pressure (MEP) for all subjects. The t-test was used to compare muscle activity between maximum lip closure and 100% MEP, and analysis of variance followed by multiple comparisons was used to compare the muscle activities observed at different expiratory pressures. [Results] No significant difference in muscle activity was observed between maximum lip closure and 100% MEP. Analysis of variance with multiple comparisons revealed significant differences among the different expiratory pressures. [Conclusion] Orbicularis oris muscle activity increased with increasing expiratory resistive loading.